Positive Politeness Strategies Performed by International Guest Speakers in Mata Najwa Exclusive Interview - Bintangtricahya, Erlin; Hartono, Rudi; Saleh, Mursid (English Education Journal, 2023)
It is necessary to recognize particular communication strategies in order to construct a decent conversation and social relationship amongst interlocutors from diverse cultures and norms. Politeness is one of the communication strategies used to maintain the interlocutors’ feeling so the conversation flows in harmony. In society, interview and talk show becomes popular programs in acquiring information. This study aims to examine the positive politeness strategies performed by international guest speakers in Mata Najwa Exclusive Interview. As the primary source, the data were taken from the interview’s transcript. A descriptive qualitative method was used to analyze the positive politeness strategies proposed by Brown and Levinson. The findings show that there are 13 types of positive politeness sub-strategies performed by four international guest speakers. Those are noticing (attending to the hearer), exaggerating, intensifying, using in-group identity markers, seeking agreement, avoiding disagreement, presupposing/asserting/raising common ground, joking, asserting/presupposing speaker knowledge, offering/promising, include both speaker and hearer in the activity, give/ask for a reason, give gifts (sympathy, good, understanding). The highest number of sub-strategy was presupposing/asserting/raising common ground which occurred 19 times. This study is expected to contribute in English language teaching specifically in comprehending cross-cultural understanding (CCU) in relation to Indonesian context.